(untitled) (Asian Journal of Medical and Biological Research, 2022)
The experiment was conducted at Horticultural Farm, Sher-e-Bangla Agricultural University, during the period from October 2018 to February 2019 to study the application of nutrient sources interaction with NAA for higher growth and quality yield of purple cabbage. The experiment consists of two factors. Factor A: F0: control, F1: vermicompost (10 t/ha), F2: N180kg.ha-1; P66kg.ha-1 K75kg.ha-1 and F3: ½ vermicompost (5t. ha-1) + N90kg.ha-1; P33kg.ha-1 K38kg.ha-1 Factor B: four levels of NAA, N0: 0 ppm, N1: 20 ppm, N2: 40 ppm and N3:80 ppm was used for the present study. The experiment was carried out in RCBD with three replications. Results showed that the highest yield of purple cabbage (27.38 t/ha) was found from the mixture of vermicompost and NPK treatment and the lowest yield (16.05 t/ha) was found from the control treatment. For different levels of NAA, the highest yield of purple cabbage (25.39 t/ha) was found from the N2 (40 ppm) treatment and the lowest yield (15.41 t/ha) was found from N0 (control) treatment. In the case of combined effect, the highest yield of purple cabbage (36.80 t/ha) was obtained from F3N2 (½ vermicompost and ½ NPK doses + 40 ppm NAA) treatment combination, and the lowest yield (6.64 t/ha) was found from F0N0 (control) treatment combination. Asian J. Med. Biol. Res. 2022, 8 (3), 154-164